2016
DOI: 10.1002/adsc.201600562
|View full text |Cite
|
Sign up to set email alerts
|

A Convenient Ruthenium‐Catalysed α‐Methylation of Carbonyl Compounds using Methanol

Abstract: An efficient ruthenium catalyst is reported, for the first time, to catalyse the α‐methylation of ketones and esters using methanol as a green methylating agent. The in situ generated catalyst from the complexes [RuCp*Cl2]2 or [RuCp*Cl2]n with dpePhos provided up to quantitative yields in the presence of only 20 mol% of lithium tert‐butoxide (LiO‐t‐Bu) as a base. Regioselective mono‐ or multi‐methylation could be effectively controlled by temperature. This catalyst system was also effective for the one‐pot seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 65 publications
0
39
0
Order By: Relevance
“…The reactions between acetophenone 1b , methanol and either benzyl alcohol 5a or 4‐methoxybenzyl alcohol 5b successfully gave 6a and 6b in good yields (56 % and 58 %, respectively). Such reactions have already been studied by other groups with expensive noble metal catalyst only, such as Ru,[13b] Ir[12a] and Pd. [19b] Therefore, the promising results in this work constitute the first example of a three‐component cross‐alkylation‐methylation of ketones with methanol and higher alcohols catalyzed by a supported non‐noble metal.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reactions between acetophenone 1b , methanol and either benzyl alcohol 5a or 4‐methoxybenzyl alcohol 5b successfully gave 6a and 6b in good yields (56 % and 58 %, respectively). Such reactions have already been studied by other groups with expensive noble metal catalyst only, such as Ru,[13b] Ir[12a] and Pd. [19b] Therefore, the promising results in this work constitute the first example of a three‐component cross‐alkylation‐methylation of ketones with methanol and higher alcohols catalyzed by a supported non‐noble metal.…”
Section: Resultsmentioning
confidence: 99%
“…In the past decade, methanol has been successfully used for the α‐methylation of ketones through the borrowing hydrogen methodology (Scheme ). This reaction has been mainly reported with homogeneous Ir, Ru and Rh complexes (Scheme a). More recently, it has been shown that non‐noble metal complexes of Co, Mn, Ni and Fe could efficiently catalyze this reaction (Scheme b).…”
Section: Introductionmentioning
confidence: 95%
“…Applying optimized conditions, a series of functionalized ketones including heterocyclic and aliphatic ones are converted into their corresponding methylated or dimethylated products in low to high yields (23–95%) (Scheme 21A). This procedure also allowed for the catalytic α ‐methylation of challenging ester derivatives, which have been less explored [19b] . Several aryl acetic esters were methylated with methanol in moderate to good isolated yields (20–95%) (Scheme 21B).…”
Section: Manganese‐catalyzed C‐methylation Reactions Using Methanolmentioning
confidence: 99%
“…Very recently,S eayad and co-workers [20] developed an elegant procedure for the a-methylation of ketones with ruthenium catalysts (Figure 3a). Key to success was the use of RuCp*(dpePhos)Cl as the catalyst along with as ubstoichiometric amount of LiOtBu as the base.A side from ketones, this catalyst system enabled the methylation of alcohols ( Figure 3b…”
Section: A-methylation Of Ketones With Methanol By Hydrogen Transfer mentioning
confidence: 99%